Markers of cochlear inflammation using MRI. Issue 1 (15th April 2013) - Floc'h, Johann Le; Tan, Winston; Telang, Ravindra S.; Vlajkovic, Srdjan M.; Nuttall, Alfred; Rooney, William D.; Pontré, Beau; Thorne, Peter R.
<x xml:space="preserve">Abstract</x> Purpose To quantify spatial and temporal inflammation‐induced changes in vascular permeability and macrophage infiltration in guinea‐pig (GP) cochlea using MRI. Materials and Methods GPs were injected with lipopolysaccharide (LPS) to induce cochlear inflammation. One group was injected with a gadolinium based contrast agent (GBCA) and dynamic contrast enhanced (DCE)‐MRI was performed at 4, 7, and 10 days after LPS treatment. A two‐compartment pharmacokinetic model was used to determine the apparent rate constant of GBCA extravasation (Ktrans). A second group was injected with ultrasmall superparamagnetic iron oxide particles (USPIOs) and studied at 2, 3, and 7 days after LPS treatment to detect tissue USPIO uptake and correlate with histology. For both groups, control GPs were scanned similarly. Results The signal enhancement increased substantially and more rapidly at day 4 in LPS‐treated than in control cochlea shortly following GBCA injection. Ktrans of LPS‐treated cochlea was maximum on day 4 at 0.0218 ± 0.0032 min−1 and then decreased to control level at 0.0036 ± 0.0004 min−1 by day 10. In the second group, the relative signal intensity and T2 in cochlear perilymphatic spaces on day 2 decreased, on average, by 54% and 45%, respectively, compared with baseline and then remained under control levels by day 7. This suggests the infiltration of inflammatory cells, although unconfirmed by histology. Conclusion This provides the first measurement of cochlear vascular permeability using MRI and a quantitative evaluation of the development of cochlear inflammation. MRI holds considerable potential for the assessment of disease processes such as clinical diagnosis of conditions such as labyrinthitis. J. Magn. Reson. Imaging 2014;39:150–161. © 2013 Wiley Periodicals, Inc.